(untitled) - Eckenfelder, W. Wesley (Singapore, 1989)
This classic text is intended for the student in courses related to industrial water pollution control, as well as a guide for someone in the industry. It is very strong on biological treatment and reflects better than any other book actual industrial treatment practices. This new revision contains new material on hazardous waste disposal and improved coverage of adsorbtion and partionaing.
Keywords: Factory and trade waste,Sewage; Purification